The activation of Epimedium polysaccharide-propolis flavone liposome on Kupffer cells. (20th November 2015) - Fan, Yunpeng; Ren, Meimei; Hou, Weifeng; Guo, Chao; Tong, Dewen; Ma, Lin; Zhang, Weimin; He, Mengmeng; Song, Xiaoping
Highlights: EPL could significantly induce the production of NO, iNOS and chemokines in KCs. EPL could significantly promote the expression of cytokines, CD11b and CD68 in KCs. EPL could significantly improve the pinocytic and phagocytic activity of KCs. EPL could significantly enhance the antigen presenting ability of KCs. EPL could strongly activate KCs compared with EP. Abstract: Epimedium polysaccharide-propolis flavone liposome (EPL), a potent immunological pharmaceutical preparation, was investigated for the immunomodulatory activity on Kupffer cells (KCs) in vitro. The results showed that EPL could significantly induce the secretion of chemokines (RANTES and MCP-1), promote the production of nitric oxide and induced nitric oxide synthase, improve the pinocytic and phagocytic activity of KCs, promote the mRNA expression of TNF-α and IL-1β, and enhance the expression of costimulatory molecules (CD11b and CD68) in KCs compared with Epimedium polysaccharide-propolis flavone (EP) at 30–7.5 μg/mL. In addition, the abilities of KCs on stimulating lymphocytes proliferation and antigen presenting were significantly enhanced after stimulated with EPL compared with EP. These results suggested that EPL could activate KCs and possessed the stronger immunomodulatory effect, which provided the theoretical basis for further studying the mechanism of EPL on improving the immune response.